Formulation, Optimization, and Characterization of Repaglinide Loaded Nanocrystal for Diabetes Therapy. (29th March 2015) - Shinde, Gajanan; Patel, Mitesh; Mehta, Manan; Kesarla, Rajesh; Bangale, Ganesh
Abstract : The aim of the present investigation was to formulate and characterize nanocrystal formulation of Repaglinide for diabetes therapy. Formulation was done by high pressure homogenization. HPH pressure and cycles range were screened by preliminary batches (T1 and T2). 5, 8, and 10 cycles and 500 to 1500 bar pressure range had kept for further investigation. Taguchi design was used to optimize type of polymer, % polymer concentration, number of cycles, and HPH pressure for nanocrystal formulation. Formulations were characterized for particle size, zeta potential, and in vitro drug release. Optimized formulation (NC 3) showed particle size of 187 nm, zeta potential of −29.4 mv, and % drug release of 80.58% and it was used for further study. Data analysis proved significant effects of factors on responses. Polydispersity index (PDI) Analysis of optimized formulation were found to be 0.248. SEM showed nanocrystal aggregation of drug, may be due to water removal process. DSC showed slight change in crystallinity, may be due to the presence of PEG 4000. Stability study was carried out for 3 months. It indicated no significant change in particle size and zeta potential. However, further studies in higher animals and human being need to be performed before this formulation can be commercially exploited.